Juvenile Hippocampal CA2 Region Expresses Aggrecan - Noguchi, Asako; Matsumoto, Nobuyoshi; Morikawa, Shota; Tamura, Hideki; Ikegaya, Yuji (Frontiers in Neuroanatomy, 2017)
Perineuronal nets (PNNs) are distributed primarily around inhibitory interneurons in the hippocampus, such as parvalbumin-positive interneurons. PNNs are also present around excitatory neurons in some brain regions and prevent plasticity in these neurons. A recent study demonstrated that PNNs also exist around mouse hippocampal pyramidal cells, which are the principle type of excitatory neurons, in the CA2 subregion and modulate the excitability and plasticity of these neurons. However, the development of PNNs in the CA2 region during postnatal maturation was not fully investigated. This study found that a main component of PNNs, aggrecan, existed in the pyramidal cell layer of the putative CA2 subarea prior to the appearance of the CA2 region, which was defined by the CA2 marker protein regulator of G protein signaling 14 (RGS14). We also found that aggrecan immunoreactivity was more evident in the anterior sections of the CA2 area than the posterior sections, which suggests that the function of CA2 PNNs varies along the anterior-posterior axis.